Multi-system measurement of aerodynamic loads - Іщенко, С.О.; Бондар, О.В. (Proceedings of National Aviation University (archive), 2009)
The basic features of projection and manufacture of multicomponent system of measurement of aerodynamic loads of beam type are observed. The previous estimation of metrology performances of the gained system is conducted.